Clinical Diagnosis and Management of Hypertension Compared With the Joint National Committee 8 Panelists' Recommendations. Issue 6 (9th June 2015) - Snipelisky, David; Waldo, Oral; Burton, M. Caroline
ABSTRACT Background The panelists of the Joint National Committee recently published new recommendations for the management of hypertension. Our study aims to evaluate how current practice compares. Hypothesis Current practice likely deviates from the recent JNC 8 panelists' recommendations. Methods A survey was sent to cardiology providers at 3 academic medical centers: Mayo Clinic, Jacksonville, Florida; Mayo Clinic, Scottsdale, Arizona; and Mayo Clinic, Rochester, Minnesota. Providers were asked to select which blood‐pressure goal would be deemed appropriate in various cases based on individual practice in both the maintenance of patients already on therapy as well as threshold of when to initiate therapy. Comparisons with current recommendations were made, as well as geographic location and level of experience. Results A total of 251 survey requests were sent (May 2014), and 77 responses (30.7%) were received. Cardiologists tended not to practice according to the new guidelines, with most variation seen in patients age >60 years without comorbidities on active treatment. Providers' selection of initial pharmacologic agents in non–African American patients, African American patients, and patients with diabetes mellitus reflected congruency with guidelines. Conclusions Our study found that clinical practice does not correlate well with the new blood‐pressure goal recommendations published by the Joint National Committee 8 panelists, particularly in patients age >60 years. Practitioners are likely to follow the recommendations in regard to pharmacologic management.